Influence of Deformation and Fluids on Ti Exchange in Natural Quartz - Bestmann, Michel; Pennacchioni, Giorgio; Grasemann, Bernhard; Huet, Benjamin; Jones, Michael W. M.; Kewish, Cameron M. (Journal of Geophysical Research. Solid Earth, 2021)
Using a combination of microstructural, spectroscopic, and geochemical analyses, we investigate how subgrain rotation recrystallization and fluid migration affect Ti concentration [Ti] in naturally deformed quartz veins from the Prijakt Nappe (Austroalpine Unit, Eastern Alps). These coarse-grained quartz veins, that formed at amphibolite facies conditions, were overprinted by lower greenschist facies deformation to different degrees. During the overprint, subgrain rotation recrystallization was dominant during progressive deformation to ultramylonitic stages. The initial [Ti] (3.0-4.7 ppm) and cathodoluminescence (CL) signature of the vein crystals decrease during deformation mainly depending on the availability of fluids across the microstructure. The amount of strain played a subordinate role in resetting to lower [Ti] and corresponding darker CL shades. Using a microstructurally controlled analysis we find that the most complete re-equilibration in recrystallized aggregates ([Ti] of 0.2-0.6 p.m.) occurred (a) in strain shadows around quartz porphyroclasts, acting as fluid sinks, and (b) in localized microshear zones that channelized fluid percolation. [Ti] resetting is mainly observed along wetted high angle boundaries (misorientation angle >10-15 degrees), with partial [Ti] resetting observed along dry low angle boundaries (<10-15 degrees). This study shows for the first time that pure subgrain rotation recrystallization in combination with dissolution-precipitation under retrograde condition provide microstructural domains suitable for the application of titanium-in-quartz geothermobarometry at deformation temperatures down to 300-350 degrees C.
CRIS-Team WoS Importer:2022-02-25